2021
DOI: 10.2196/26683
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Six-Week-Long Therapist-Guided Online Therapy Versus Self-help Internet-Based Therapy for COVID-19–Induced Anxiety and Depression: Open-label, Pragmatic, Randomized Controlled Trial

Abstract: Background The COVID-19 pandemic has led to a notable increase in psychological distress, globally. Oman is no exception to this, with several studies indicating high levels of anxiety and depression among the Omani public. There is a need for adaptive and effective interventions that aim to improve the elevated levels of psychological distress due to the COVID-19 pandemic. Objective This study aimed to comparatively assess the efficacy of therapist-gui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
99
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(107 citation statements)
references
References 26 publications
3
99
0
5
Order By: Relevance
“…The 6 trials 25-30 that tested standard interventions minimally adapted for mental health during COVID-19 were conducted in Oman (N = 46), 25 Malaysia (N = 61), 26 Spain (N = 164), 27 Iran (N = 150), 28 Serbia (N = 104), 29 and China (N = 104). 30 Participants were recruited via social media, 26,29 an internet survey, 25 and a university email list; 27 in 2 trials, recruitment method was not reported.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 6 trials 25-30 that tested standard interventions minimally adapted for mental health during COVID-19 were conducted in Oman (N = 46), 25 Malaysia (N = 61), 26 Spain (N = 164), 27 Iran (N = 150), 28 Serbia (N = 104), 29 and China (N = 104). 30 Participants were recruited via social media, 26,29 an internet survey, 25 and a university email list; 27 in 2 trials, recruitment method was not reported.…”
Section: Resultsmentioning
confidence: 99%
“…The 6 trials 25-30 that tested standard interventions minimally adapted for mental health during COVID-19 were conducted in Oman (N = 46), 25 Malaysia (N = 61), 26 Spain (N = 164), 27 Iran (N = 150), 28 Serbia (N = 104), 29 and China (N = 104). 30 Participants were recruited via social media, 26,29 an internet survey, 25 and a university email list; 27 in 2 trials, recruitment method was not reported. 28,30 Two trials tested standard cognitive behavioural therapy delivered individually (6 sessions) 25 or in groups (10 sessions) 28 ; both reported targeting mental health symptoms from COVID-19, but neither described COVID-19-specific intervention adaptations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations